2020
DOI: 10.1038/s41598-020-58815-9
|View full text |Cite
|
Sign up to set email alerts
|

Shoes with active insoles mitigate declines in balance after fatigue

Abstract: fatigue can induce postural instability and even lead to falls. However, most current methods to delay or reduce fatigue require long preparatory time, or large and expensive equipment. We propose a convenient method to alleviate postural instability due to fatigue. We paid attention to that fatigue and aging share similar neurophysiological deterioration of sensory-motor function. considering that stochastic resonance via sub-sensory mechanical vibration increases postural stability in the elderly, we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…where K LQR is the optimal control gain matrix found via the LQR procedure. The matrices Q and R in (5) weight the state and input deviations from zero in the cost function.…”
Section: The Linear Quadratic Regulatormentioning
confidence: 99%
“…where K LQR is the optimal control gain matrix found via the LQR procedure. The matrices Q and R in (5) weight the state and input deviations from zero in the cost function.…”
Section: The Linear Quadratic Regulatormentioning
confidence: 99%
“…Consistent behavioral patterns observed across subjects, represented by descriptive measures such as center of mass (COM) or center of pressure (COP) motion, suggest strategies to manage complex whole-body balancing in a coordinated manner [8][9][10][12][13][14]. While there is no doubt that characterizing behavioral patterns is important, it does not define the postural control strategy [1].…”
Section: Understanding Natural Balance Without Perturbationsmentioning
confidence: 99%
“…The remaining nonlinearities would either be differentiable or resemble noise, and small motions would justify a linearized representation. Indeed it has been widely reported that unperturbed human balancing exhibits subtle movement [13,27]. The stationarity of human balance is debatable [5,31,32]; due to fatigue or change in control strategy (e.g., transitioning between an 'ankle strategy' and a 'hip strategy' [28]) during balancing, the system may exhibit time-varying dynamics.…”
Section: Linear and Stationary Processesmentioning
confidence: 99%
“…These changes may increase the incidence of sport injuries [24]. To date, most fatigue and footwear studies have predominantly focused on running economy [26], subjective comfort [27] and balance control [28]. However, limited efforts have been exerted on the relationship between footwear cushioning and fatigue in basketball.…”
Section: Introductionmentioning
confidence: 99%